Strategi Dakwah Mantan Anggota Hizbut Tahrir Indonesia di Kabupaten Jember Pasca Dibubarkan Pemerintah Republik Indonesia - Firdaus, Rendi Maulana; Asror, Ahidul (Icon: Islamic Communication and Contemporary Media Studies, 2024)
Da'wah strategy is a method that is used so that da'wah strategy is a method that is used so that da'wah is accepted by others. All Islamic organizations have a da'wah strategy in terms of maintaining and increasing the number of their members, this is done by Hizbut Tahrir Indonesia. The Hizbut Tahrir organization has been legally banned, but its da'wah activities continue in the community, especially the people of Jember Regency. The focus of research in this thesis is how the da'wah strategy and forms of activities of former HTI members in Jember Regency after it was disbanded by the government of the republic of Indonesia. This study uses a descriptive qualitative approach. Determination of research subjects by purposive sampling. Data collection techniques using observation, interviews and documentation. Analysis of the data using source triangulation. The results of this study are former HTI members in Jember Regency carrying out da'wah strategies by changing the name of the organization, closed studies, preaching through the media, education, marriage and inviting local community leaders. The form of the activity is da'wah with speech, pen and action.